The debt trap, a shadow pandemic for commercial sex workers: Vulnerability, impact, and action - Shekhar, Beulah (International review of victimology, 2023)
This research paper is a stringent analysis of the condition of commercial sex workers in India and what is happening to them in this pandemic-stricken time. The study details their economic condition and what is forcing them to borrow money from treacherous lenders despite knowing the risks behind it. Apart from being exploited financially, they are also becoming vulnerable for sexual, emotional, and physical exploitation, worsening their situation even further. The research findings show that 90% of commercial sex workers in red light areas will be forced into a debt trap that is non-repayable in their lifetime, making it a massive movement of commercial sex workers entering into bonded labour, another form of modern-day slavery. Apart from the financial peril, poverty is forcing them to be in a situation of major health hazard. Being deprived of customers for so long, they might be forced to work in this uncertain situation making it an optimum ground for a super-spread of the virus. A rapid assessment method has been used to collect the data from numerous commercial sex workers across the nation. The collected data are analysed using qualitative analysis and also visualized for better understanding. As a means to provide tangible alternative solutions to the problem, the study strongly recommends occupational training programs for commercial sex workers that provide a transition into alternative livelihoods, government action against predatory high-interest loans, and the redevelopment of red light areas where economic returns can be reinvested into commercial sex worker retraining programs.